Burger's medicinal chemistry and drug discovery : volume 1 : drug discovery - Abraham, Donald J. (Hoboken, New Jersey : Wiley, 2003)
Offers access via basic and advanced search engines to broad coverage of the field of medicinal chemistry and drug discovery for medicinal chemists, biologists, pharmacologists and molecular biologists.
V. 1. Drug discovery -- v. 2. Drug discovery and drug development -- v. 3. Cardiovascular agents and endocrines -- v. 4. Autocoids, diagnostics, and drugs from new biology -- v. 5. Chemotherapeutic agents -- v. 6. Nervous system agents.
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL CHEMISTRY